Hubungan Antara Dukungan Sosial Dan Penerimaan Cinta Beda Agama Pada Remaja - Vinsensius Yohanes Resi Dadi; Markus Kandu (Institut Nalanda, 2024)
Cultural and religious diversity in Indonesia is one of the factors in the interaction between individuals with different backgrounds. This can also increase the possibility for the individual to have a dating relationship with an individual from a different group. Nowadays, many dating relationships are carried out by individuals who have different religions. The most important social support is from parents and family. Teenagers want to be cared for, cared for, loved and given support appropriate to the age at which teenagers are starting to develop. Apart from parental support, support from the environment is also very important, namely support from teachers, school friends, peers and neighbors. Social support can be applied to the adolescent environment, this support is related to children's academic needs, positive self-image, self-esteem, motivation and mental health. This research uses a library method by collecting information, analyzing and developing understanding from the information obtained. From the information obtained, it can be seen that the acceptance of love from different religions among teenagers is very closely related to the relationship between social support in the youth environment.